Bimetallic Ni-Fe Supported by Gadolinium Doped Ceria (GDC) Catalyst for CO2 Methanation - Kristiani, Anis; Takeishi, Kaoru; Jenie, Siti Nurul Aisyiyah; Petrus, Himawan Tri Bayu Murti (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
CO2 conversion into fuels and high value-added chemical feedstocks, such as methane, has gained novel interest as a crucial process for further manufacturing multi-carbon products. Methane, CH4, becomes a promising alternative for environmental and energy supply issues. Nickel-based catalysts were found to be very active and selective for CH4 production. The use of promoter and support material to develop high activity, high selectivity, and durable catalysts for CO2 methanation at low temperature is a challenge. Gadolinium-Doped Ceria (GDC) has been known as material for Solid Oxide Fuel Cell (SOFC) and Solid Oxide Electrolysis Cell (SOEC) due to higher ionic conductivity and lower operating temperatures. However, few researches have been done regarding to CO2 methanation over GDC as catalyst support so far. In this present work, CO2 methanation was investigated over bimetallic Ni-Fe catalyst supported by GDC. The results showed that CH4 production rate by using Ni-Fe/GDC catalyst was higher than that of GDC at all reaction temperatures carried on. Ni-Fe/GDC showed remarkable CH4 production rate as of 17.73 mmol.gcat−1.h−1 at 280 °C. No catalytic activity was produced by GDC catalyst only. The highest CO2 conversion (46.50%) was observed at 280 °C, with almost 100% selectivity to CH4. The turnover frequency (TOF) value of Ni-Fe/GDC (4529.32 h−1) was the highest than that of Ni and common CO2 methanation catalyst, Ni/Al2O3 catalysts at 280 °C, further displaying the outstanding low-temperature catalytic activity. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).